Identification of Science Concepts and Principles Based on Local Wisdom of Pacu Jalur to Develop Science Learning Materials - Andika Febrian*; Jumadi Jumadi (Jurnal Pendidikan Sains Indonesia, 2022)
Local wisdom in Indonesia always considered mystical and taboo to be discussed, while this will be a great potential when viewed from the point of view of science which is then identified and interpreted in the form of a study of scientific treasures. The scientific treasures of course will also be useful if they are integrated in education and used as learning materials. This study aims to identify the science concepts and principles based on local wisdom of Pacu Jalur to develop science learning materials for junior or senior high school. This research used qualitative research with the descriptive analysis of Miles and Huberman model. The sampling techniques of this research were purposive and snowball sampling that collected through the observation, in depth interview, documentation, and literature review. The result of this study indicated that pacu jalur as local wisdom and indigenous knowledge contains many values, including aspects of science. This study should be able to further add to the value of wealth, re-introduce to many people, and enthusiasm to be inherited and preserved such as being a part of local education